Green synthesis of zinc ferrite nanoparticles for photocatalysis of methylene blue. Issue 13 (9th November 2020) - Din, Muhammad Imran; Jabbar, Summiya; Najeeb, Jawayria; Khalid, Rida; Ghaffar, Tayabba; Arshad, Muhammad; Khan, Safyan A.; Ali, Shahid
Abstract: In this study, zinc ferrite nanoparticles (ZF-NPs) were synthesized using aqueous seed extract of Piper nigrum as a bio-reducing and stabilizing agent. FTIR, SEM, FE-SEM, XRD, and TGA have been used for characterizing ZF-NPs. The results showed that Piper nigrum stabilized ZF-NPs have high purity and size range of 60–80 nm. The performance of the ZF-NPs has been investigated by photocatalytic reduction of methylene blue (MB) in the presence of sunlight. The factors responsible for affecting the degradation values of the reaction were also explored for developing a better understanding of the phenomenon.